Selective power transmission using a shift in resonant frequency due to the transportation of liquid metal droplets - Shinji Bono; Hinata Mori; Ayano Shimizu; Ryotaro Nakai; Satoshi Konishi (Scientific Reports)
Abstract We devised a signal-switching mechanism (SSM) based on the transportation of liquid metal droplets (LMDs). This method transmits power selectively to the light-emitting diode (LED) connected with a pair of electrodes, including a transported LMD. When an LMD is transported through a channel between multiple pairs of electrodes, the capacitance of the pair of electrodes decreases. In the SSM, we connected the electrodes with a coil and LEDs and investigated the frequency response of the impedance of the mechanism. As a result, we find the resonant phenomena of the SSM and the shift of the resonant frequency owing to the transportation of the LMD. By applying an alternating voltage, whose frequency corresponded with that of the resonant frequency of the LED-connected SSM, we could selectively transmit power to the LED activated by an LMD. Our equivalent circuit model quantitatively predicts the transmitted power and the shift in the resonant frequency due to the transportation of LMDs. The SSM using LMDs has a promising potential to contribute to soft multiplexers without complex wiring, where they can help integrate not only multiple sensors but also actuators as well.